PENGARUH TIM KERJA, KOMUNIKASI DAN DISIPLIN KERJA TERHADAP KINERJA KARYAWAN (STUDI KASUS PT AGRO WIRA LIGATSA PASAMAN BARAT) - Dodo Mulia Saputra; Zusmawati Zusmawati (Jurnal Bina Bangsa Ekonomika, 2024)
The purpose of this study was to examine the effect of work team variables, communication and work discipline on employee performance at PT Agro Wira Ligatsa West Pasaman. This type of research uses quantitative methods, data collection through distributing questionnaires to 112 respondents using total sampling, namely non-random sampling techniques. By using instrument test testing (validity test and reliability test), classical assumption test (normality test, multicollinearity test and heteroscedasticity test) then multiple linear regression and hypothesis testing with the help of SPSS application. The results of the study indicate that work teams have a positive and significant effect on employee performance, communication has a positive and significant effect on employee performance and work discipline has no positive and significant effect on employee performance